Razlikovanje glagolskih oblik po spolu v sedanjiku dvojine greve - Jakop, Tjaša (Slavistična revija, 2007)
The article treats the differentiation between masculine and feminine verbal forms in present tense dual based on the material for the Slovene Linguistic Atlas (SLA) and on the data from the contemporary dialectological literature and the media. The author gives a geolinguistic representation of the areal of this phenomenon with two linguistic maps. She compares the present situation with historical data and the data from older dialectological literature.
Keywords: dialectology; dialektologija; dvojina; glagol; oblikoslovje; Slovene; Slovene dialects; slovenska narečja; slovenščina; spol; verb